Humeral Head Shape in Native and Prosthetic Joint Replacement. (May 2019) - Iannotti, Joseph P; Jun, Bong Jae; Teplensky, Jason; Ricchetti, Eric
Background: Nonspherical prosthetic humeral head designs have become increasingly popular as they better approximate the native shoulder anatomy and biomechanical properties and is supported by the existing literature. It remains to be seen how this will impact postoperative outcomes for total shoulder arthroplasty providing a justification for this review. Methods: A review and synthesis of the literature on the subject of joint replacement in the native and prosthetic humeral head was performed. Results: Our review encompasses the anatomical, biomechanical, and finite element data present in the literature for native and prosthetic joint replacement. They describe the native humeral head as more elliptical (nonspherical) than circular (spherical) and that nonspherical prosthetics more closely approximate glenohumeral kinematic properties. Conclusion: A nonspherical prosthetic may influence long-term clinical outcomes in hemiarthroplasty and anatomic total shoulder arthroplasty though further research in this area is necessary.